Effects of Three Different Testosterone Formulations in Female‐to‐Male Transsexual Persons. (1st December 2014) - Pelusi, Carla; Costantino, Antonietta; Martelli, Valentina; Lambertini, Martina; Bazzocchi, Alberto; Ponti, Federico; Battista, Giuseppe; Venturoli, Stefano; Meriggiola, Maria C.
Abstract: Introduction: Gender dysphoria is characterized by a strong discomfort with the gender assigned at birth and the urge to live as a member of the opposite gender. The acquisition of phenotypic features of the desired gender requires the use of cross‐sex hormones. Female‐to‐male (FtM) transsexual persons are treated with testosterone to induce virilization. Aim: The aim of the study was to assess the effects of three different testosterone formulations on body weight and composition and metabolic and bone parameters. Methods: Forty‐five FtM transsexuals were randomly assigned to receive testoviron depot (i.m.: 100 mg/10 days; n = 15), testosterone gel (50 mg/die; n = 15), and testosterone undecanoate (i.m.: 1, 000 mg every 6 weeks for the first 6 weeks and then every 12 weeks, n = 15). FtM individuals were studied before, at week 30, and at week 54 of testosterone treatment. Main Outcome Measures: Anthropometric, metabolic, bone, hematological, and biochemical parameters were evaluated at baseline and after 12 months of treatment. Results: Lean body mass significantly increased and fat mass decreased in all groups. No modifications were reported in fasting insulin and insulin sensitivity index. High‐density plasma lipoprotein levels declined significantly and low‐density lipoprotein concentrations increased significantly in the three groups. The activated partial thromboplastin time and factor I did not change while prothrombin time significantly increased in all groups. At week 54, all subjects were amenorrheic and time to amenorrhea did not differ between the three groups. Current general life satisfaction was increased in all subjects after 1 year of treatment. Conclusions: One‐year testosterone administration in FtM transsexuals appears to be very safe with no differences among the testosterone formulations used. Our study is preliminary, and the detection of subtle or long‐term differences in the effects of the three formulations may require further larger and longer term studies in this and other populations.